2012
DOI: 10.1002/mrc.2799
|View full text |Cite
|
Sign up to set email alerts
|

Conformations and intermolecular interactions pattern in solid chloroxylenol and triclosan (API of anti‐infective agents and drugs). A 35Cl NQR, 1H‐14 N NQDR, X‐ray and DFT/QTAIM study

Abstract: Two antibacterial and antifungal agents, chloroxylenol (4-chloro-3,5-dimethyl-phenol) and triclosan (5-chloro-2-(2',4'-dichlorophenoxy)-phenol), were studied experimentally in solid state with an X-ray, (35)Cl-nuclear quadrupole resonance (NQR) and (17)O-nuclear quadrupole double resonance (NQDR) spectroscopies and, theoretically, with the density functional theory/quantum theory of atoms in molecules (DFT/QTAIM). The crystallographic structure of triclosan, which crystallises in space group P31 with one molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 67 publications
(172 reference statements)
0
35
0
Order By: Relevance
“…[796][797][798][799][800][801][802][803][804] Specifically in the context of the chemical bond and intermolecular interactions, 55,[805][806][807][808][809][810][811][812][813][814][815] a traditional task is to use a series of basis sets in order to reproduce accurately the available experimental data, [816][817] in general those derived from structural and vibrational analysis. 203 Regarding the QTAIM characterization of intermolecular interactions, 212,[818][819][820][821][822][823][824][825][826][827][828][829] in particular the hydrogen bonds, it has been demonstrated that Pople's split-valence double-z incremented by polarization functions 830,831 with higher angular momentum are not appropriate for basis sets to describe the electronic density computed through the QTAIM protocols. 832 Otherwise, valence and diffuse functions fairly do it well.…”
Section: The Relationship Between Qtaim Descriptors and Quantum Chemi...mentioning
confidence: 99%
“…[796][797][798][799][800][801][802][803][804] Specifically in the context of the chemical bond and intermolecular interactions, 55,[805][806][807][808][809][810][811][812][813][814][815] a traditional task is to use a series of basis sets in order to reproduce accurately the available experimental data, [816][817] in general those derived from structural and vibrational analysis. 203 Regarding the QTAIM characterization of intermolecular interactions, 212,[818][819][820][821][822][823][824][825][826][827][828][829] in particular the hydrogen bonds, it has been demonstrated that Pople's split-valence double-z incremented by polarization functions 830,831 with higher angular momentum are not appropriate for basis sets to describe the electronic density computed through the QTAIM protocols. 832 Otherwise, valence and diffuse functions fairly do it well.…”
Section: The Relationship Between Qtaim Descriptors and Quantum Chemi...mentioning
confidence: 99%
“…Adsorption of TCS might occur in one of the preferred conformations, which have prior been determined by quantum chemical calculations. 23,24 In this optimized geometry, TCS has a twisted conformation in the solid state with a dihedral angle of 62°between the dichlorobenzene and phenolic ring due to the steric effect between the ortho-chlorine and ortho-hydroxyl substituents. Sorption of TCS could occur in a geometry that minimizes steric hindrance.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…One reason for the inhibition of DCDD formation could be that the necessary conformation for the nucleophilic substitution could not be adopted in the sorbed state and that the transition state for an intramolecular substitution was less favorable in the sorbed state as compared to freely dissolved TCS. Adsorption of TCS might occur in one of the preferred conformations, which have prior been determined by quantum chemical calculations. , In this optimized geometry, TCS has a twisted conformation in the solid state with a dihedral angle of 62° between the dichlorobenzene and phenolic ring due to the steric effect between the ortho-chlorine and ortho-hydroxyl substituents. Sorption of TCS could occur in a geometry that minimizes steric hindrance.…”
Section: Resultsmentioning
confidence: 99%
“…In both polymorphs, common structural motifs are molecules linked by NH•••π interactions with the locking ability of the rings conformation, 70 indicate a significant thermal hysteresis, defined here as the difference between the melting and freezing points.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In both polymorphs, common structural motifs are molecules linked by NH···π interactions with the locking ability of the rings conformation, but, in form I two neighboring molecules are mutually linked and form hydrogen-bonded dimeric synthons, while in form II chains of molecules are formed, Figure S2 (Supporting Information). These packing motifs are kept unchanged upon cooling/heating in each form.…”
Section: Resultsmentioning
confidence: 99%